Pengaruh Variasi Produk, Store Atmosphere Dan Lokasi Terhadap Minat Beli Ulang Pada Kopi Studio 24 Di Kota Malang (Studi Kasus Mahasiswa Di Kota Malang) - Mardhiyyah, Nafisatul Itsna; Nurhidayah, Nurhidayah; Sholehuddin, Sulton (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This research aims to identify “the influence of product variations, store atmosphere and location on repurchase interest in Studio 24 coffee in Malang City, a case study of Malang City students”. This research uses a quantitative approach method. The data analysis technique in this research uses multiple linear regression analysis. The population in this study was Studio 24 Coffee's Instagram followers, totaling 16,800. The sample was taken using the Slovin formula and the sample size was 99. The respondent criteria used were Malang City students who had purchased Studio 24 Coffee products more than 3 times. The results of this research show that there is a positive and significant influence between the variables of product variation, store atmosphere and location on repurchase interest in Studio 24 coffee in Malang City. And also, the variables of product variation, store atmosphere, and location have a partial and simultaneous influence on the repurchase interest variable at Studio 24 Coffee in Malang City. Keywords: Product Variation, Store Atmosphere, Location, Repurchase Interest